Mobile Phone Data and Mobility Policy - Pucci, Paola (TeMA - Journal of Land Use, Mobility and Environment, 2013)
The paper focusses on the potentialities offered by mobile phone data to provide useful knowledge of site practices and rhythms of usage of contemporary city, for more effective and equitable mobility policies.Starting from the results of a research carried out at the Politecnico di Milano, using mobile phone data provided by Telecom Italia and finalized to verify the meaning of mobile phone data in returning the density of land use (Manfredini, Pucci & Tagliolato, 2012 and 2013) and the origins and destinations of daily movements (Tagliolato, Manfredini & Pucci, 2013), we will highlight how new maps, based on the processing of mobile phone data can represent spatialized urban practices and how they can give new insights for analyze space-time patterns of mobility practices. In our research, mobile phone data, returning new maps of site practices in Lombardy Region with information on temporary populations and city usages patterns (daily/nightly practices, non-systematic mobility), allowed to trace “fuzzy boundaries” as perimeters of practices, proposed like a tool for supporting and increasing the efficiency of urban policies and mobility services.In the paper, the identification of temporary urban populations through two types of mobile phone data (density of the calls and origin - destination traces of the calls) has not only a knowing purpose, but it is the condition for recognize new claims referred to “communities of practice”, by which to build mobility policies incisive, also because not generalist.